2022
DOI: 10.3390/microorganisms10081487
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Coexistence, and Correlations between Seven Pathogens Detected by a PCR Method from South-Western Poland Dairy Cattle Suffering from Bovine Respiratory Disease

Abstract: Bovine respiratory disease (BRD) is a very important disease that contributes to economic losses in dairy and beef cattle breeding worldwide. The molecular testing of material from 296 calves showing BRD symptoms from 74 dairy herds located in south-western Poland was performed in 2019–2021. Molecular tests were performed using a commercial kit “VetMAXTM Ruminant Respiratory Screening Kit” (Thermo Fisher Scientific) for the simultaneous detection of genetic material of seven pathogens responsible for BRD. At l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
“…Three concomitant respiratory infections were identified during this investigation, all including the participation of OvGHV2, with the simultaneous detection of BoGHV6 (n = 2) and BCoV (n = 1) from the DNS of two calves with respiratory distress and one calf with diarrhea. Similar findings of simultaneous agents associated with the development of BRD were described worldwide in dairy 34,57,58 and feedlot 29,34,59,60 cattle worldwide, indicating that this is a common phenomenon of cattle with pulmonary disease. Although the possible role of BoGHV6 in the development of diseases in ruminants remains controversial 22 , several studies have associated this pathogen with a wide range of diseases syndromes, including proliferative lesions 20,21 , as wells as pulmonary 17 , intestinal 17 , and reproductive 23,24,26,27 alterations.…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were identified in dairy calves from Southern Brazil [ 39 ] and Denmark [ 11 ]. Alternatively, P. multocida was predominant within dairy calves from Southern Brazil [ 24 ], Finland [ 21 ], and Poland [ 40 ]. Furthermore, neither of these pathogens and only M. bovis and mollicutes were detected in a study from Southeastern Brazil [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neither of these pathogens and only M. bovis and mollicutes were detected in a study from Southeastern Brazil [ 41 ]. The basic difference in these studies was the methodology used, with molecular diagnostics being performed in the investigations in Southern Brazil [ 39 ] and Europe [ 11 , 21 , 40 ], as opposed to the conventional bacteriological techniques (isolation and culture) performed in the study from Southeastern Brazil [ 41 ]. Consequently, these differences in the detection levels are primarily due to the elevated sensitivity and specificity associated with the molecular techniques compared to the traditional methods of bacterial culture and isolation.…”
Section: Discussionmentioning
confidence: 99%
“…BCoV infection is more frequent in younger cattle and it is associated with bovine respiratory complex (BRD) in calves 33 . Coronavirus was detected in one-third of calves affected by BRD in the country, indicating its importance in the complex aetiology of the disease 42 . This contrasts with low (6.8%) BCoV seroprevalence among European bison and a strong correlation between age and the serological status with no seropositives among the youngest animals.…”
Section: Discussionmentioning
confidence: 99%